Pengaruh Current Ratio, Debt To Equity Ratio, Debt Ratio Dan Net Profit Margin terhadap Return On Investment Perusahaan Jasa Telekomunikasi yang terdaftar di Bursa Efek Indonesia (BEI) - Hartina Hartina; Roni Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2018)
AbstractThis study aims to determine the effect of Current Ratio, Debt to Equity Ratio, Debt Ratio, and Net Profit Margin to Return on Investment Telecommunication service companies listed in Indonesia Stock Exchange (BEI). In this study, the researcher used quantitative method which consist of five variables, including Current Ratio, Debt to Equity Ratio, Debt Ratio and Net Profit Margin as independent variables and Return on Investment as a dependent variable. The technique used for sampling using purposive sampling so that obtained by fourcompany. The result of this research based on result of regression analysis show that Current Ratio has value equal to 0,942 with significant value t> 0,05 (0,355> 0,05), means that Current Ratio has effect negatively and significant to Return on Investment, Debt to Equity Ratio has value equal to -2,945 with significant value t<0,05 (0.007 <0.05), means that Debt to Equity Ratio has effect positively and significant to Return on Investment, Debt Ratio has a value of -0.2244 with significant value t>0.05 (0.809> 0.05), means that Debt Ratio has effect negatively and significant to Return on Investment, Net Profit Margin has a value of 0.667 with significant value t <0,05 (0,510 <0,05, means that Net Profit Margin has effect negatively and significant to Return on Investment. Keywords: Return on Investment, Current Ratio, Debt to Equity Ratio, Debt Ratio, and Net Profit Margin.